Tren Teknologi Artificial Intelligence Pengganti Model Iklan Di Masa Depan - Raihani Alvinna Fitriyani; Lintang Tirta Putri; Robiatul Adawiyah (Journal Social Politica, 2021)
The use of technology is increasing rapidly as the times progress and the benefits and influences produced. New digital technologies have dramatically changed the way companies interact with consumers. The development of technology that is developing rapidly today is Artificial Intelligence or AI. Artificial Intelligence is a technology developed for a long time by experts. This technology is made similar to human intelligence so it is often called artificial intelligence. The development of Artificial Intelligence is very rapid growth in the field of media and information. Recently, there began to be a development using the Artificial Intelligence model to be used as an advertising model. This advertising model was enthusiastically welcomed by the public, but artificial intelligence technology can have cultural impact and influence by bringing new globalization. For now some topics can be applied widely to the development of Artificial Intelligence in lieu of advertising models and can be proposed for future research. In the future, the development of the Artificial Intelligence model is considered to eliminate artists who have been in the world of advertising for a long time because by using the human Artificial Intelligence model more freely in regulating the model and considered more practical. Seeing the rapid growth of technology the use of Artificial Intelligence is predicted to replace human jobs in the world of the information media industry. Actually, this has a good positive impact on the industrial world because it can make production performance in the field more quickly resolved but there will be many humans who are difficult to find work because it is replaced by Artificial Intelligence technology.